Use of Telemedicine in a Sports Medicine Clinic: An Investigation of Patient Satisfaction - Kelly Harrington; Lindsey Eberman; Matthew Rivera; J'nai Pittman; Shelby Broughton; Regina Hash (Bowling Green State University, 2024)
Objective: Compare patient satisfaction between telemedicine and in-office visits and between providers post-operatively in an orthopedics setting with athletic trainers and physicians. Design: Cross-sectional study Methods: Patients from a Sports Medicine Clinic that received an orthopedic surgical intervention from March 2020-September 2021, and engaged in telemedicine, or an in-office visit post-operatively. Provider type included full-time athletic trainers, resident athletic trainers, physician (MD) resident/fellows, and float athletic trainers. Press-Ganey Patient Experience Surveys were collected at the time of follow up visit, with focus on items, "likelihood to recommend" and "how well staff worked together." Results: There was a total of 255 patients (age=50±17 years). Providers included the attending physician with full-time athletic trainers (n=134, 52.3%), resident athletic trainers (n=77, 30.1%), MD residents/fellows (n=38, 14.8%), or float athletic trainers (n=6, 2.3%). No significant difference was found with patient satisfaction between in-office (n=175, 68.4%), or telemedicine visits (n=80, 31.3%), (p>.44). Patients were more satisfied with care provided by the full-time athletic trainers compared to MD residents/fellows (p.18). Conclusions: This study demonstrates no significant differences with patient satisfaction between in-office or telemedicine visits. Patients seeing full-time athletic trainers had the highest patient satisfaction, demonstrating the capability of athletic trainers to effectively use telemedicine in a physician practice.